Mass Mobilization in Indian Politics: A Case Study of Non-Cooperation Movement - Dar, Farooq Ahmad; Khan, Muhammad Sajid; Zahoor, Muhammad Abrar (Journal of History Culture and Art Research, 2021)
Mass-Mobilization is one of the key ingredients for not only launching a movement but also for spreading any political agenda. The involvement of the masses always plays an important role in a process of bringing change anywhere and at any time. The history of South Asia, however, witnessed that in the struggle against the colonial rulers, to begin with, started by the elite alone. Politics was considered as the domain of a selected few and the common men were considered as ignorant and perhaps irrelevant and thus were kept at a distance. It was only after the beginning of the twentieth century and especially after the entrance of Gandhi on the political screen that the masses gained importance and were directly involved in political affairs. They not only became part of the Non-Cooperation Movement but also played an important role in spreading the movement all across India. In this paper, an attempt has been made to highlight Gandhi’s efforts to mobilize Indian masses during the Non-Cooperation Movement and its impact on the future politics of the region. The paper also discusses in detail different groups of society that actively participated in the process of mass-mobilization.